Microstructure evaluation of shear bands of microcutting chips in AA6061 alloy under the mechanochemical effect. (20th November 2021) - Zhang, Jiayi; Lee, Yan Jin; Wang, Hao
Highlights: Microstructure characterization is conducted on shear bands of microcutting chips with EBSD and TEM. The surfactant-affected chip shows much coarser grains than the surfactant-free chip. Almost no recrystallization phenomenon is observed inside the surfactant-free shear band. Fewer subgrains and dislocations are observed inside the shear band with mechanochemical effect. The main dislocation motion in shear bands for surfactant-free and surfactant-affected chips are dislocation climb and dislocation glide, respectively. Abstract: The mechanochemical effect on the microcutting of AA6061 alloy is studied through characterization on the chip. A pronounced reduction of machining forces and chip thickness was observed with mechanochemical effect during microcutting. Furthermore, electron backscattered diffraction (EBSD) and transmission electron microscopy (TEM) observations were performed on the chips and shear bands. The result reveals much coarser grains (24.6 μm in size) in the surfactant-affected chip than that in the surfactant-free chip (13.5 μm). Different grain orientations are induced by microcutting. {100}<001> and {110}<112> grain orientations are majority for surfactant-free chip, and {110}<001> and {100}<110> dominate most for all grain orientations for surfactant-affected chip. Additionally, since less localized shear strain and lower temperature are generated inside the shear band with mechanochemical effect, almost no recrystallization phenomena can be observed in this region. TEM analysis shows that fewer subgrains and dislocations could be observed inside the shear band of the surfactant-affected chip in comparison with the surfactant-free chip. Based on the high-resolution transmission electron microscopic (HRTEM) observations, dislocations were observed at the atomic scale. The results show that the main dislocation motion mode in shear bands of surfactant-free and surfactant-affected chips are dislocation climb and dislocation glide, respectively.